2017
DOI: 10.1111/bjh.14724
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and genetic predictors of renal dysfunctions in sickle cell anaemia in Cameroon

Abstract: SUMMARY Micro-albuminuria and glomerular hyperfiltration are primary indicators of renal dysfunctions in Sickle Cell Disease (SCD), with more severe manifestations previously associated with variants in APOL1 and HMOX1 among African Americans. We have investigated 413 SCD patients from Cameroon. Anthropometric variables, haematological indices, crude albuminuria, albumin-to-creatinine ratio (ACR) and estimated glomerular filtration rate (eGFR) were measured. Patients were genotyped for 3.7 kB alpha-globin gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
91
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(109 citation statements)
references
References 68 publications
12
91
6
Order By: Relevance
“…Two SNPs were monomorphic in both patients and controls: HBS1L-MYB -rs9376090 and ADRA2A -rs3750635; OPRM1 -rs1799971 was monomorphic among controls and very rare (0.001) in patients. Only the 3.7del α-globin gene genotypes (p = 0.005) were out of HWE; however, this deviation was expected in view of the strong protective effect of this genetic variant on SCD, as previously reported on Cameroonians (Geard et al , 2017, Rumaney et al , 2014). The skewness of VOC, and hospitalisation, consultation rates and haematological indices, was corrected by taking their natural logarithm to approximate normal distribution.…”
Section: Methodssupporting
confidence: 58%
See 2 more Smart Citations
“…Two SNPs were monomorphic in both patients and controls: HBS1L-MYB -rs9376090 and ADRA2A -rs3750635; OPRM1 -rs1799971 was monomorphic among controls and very rare (0.001) in patients. Only the 3.7del α-globin gene genotypes (p = 0.005) were out of HWE; however, this deviation was expected in view of the strong protective effect of this genetic variant on SCD, as previously reported on Cameroonians (Geard et al , 2017, Rumaney et al , 2014). The skewness of VOC, and hospitalisation, consultation rates and haematological indices, was corrected by taking their natural logarithm to approximate normal distribution.…”
Section: Methodssupporting
confidence: 58%
“…It is therefore reasonable to envisage expending future explorations with genome-wide association studies, and targeted deep sequencing of genes in the inflammatory pathways, in SCD patients living in Africa. Nearly half of the participants (46.6 %) had frequent VOC episodes, much higher than the 5.2% reported in the CSSCD (Platt et al , 1991), revealing a particular severity of this disease in Cameroon (Wonkam et al , 2014a; Njamnshi et al , 2006; Geard et al , 2017). But this higher rate of pain could also be attributed to a selection bias, due to hospital-based recruitment, and the cross-sectional and retrospective nature of the VOC phenotype.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Similarly, α-thalassemia was significantly associated with the absence of hyperfiltration in a young adult population of SCA patients [61]. Another recent study in a cohort of 413 SCD individuals from Cameroon also demonstrated a ‘protective’ association between α-thalassemia and macroalbuminuria [62]. …”
Section: Modifying Factorsmentioning
confidence: 99%
“…Another smaller study of 152 SCD patients in Europe failed to delineate a relationship between the HMOX1 rs743811 variant and kidney disease [70]. However, another study of young SCD patients (median age 15 years) from Cameroon demonstrated a trend to association between HMOX1 rs743811 and macroalbuminuria, although this did not quite reach statistical significance ( p = 0.06) [62]. While certainly not definitely associated with kidney disease in SCD, these HMOX1 variants do warrant additional examination, particularly due to their direct influence on heme catabolism and potential pathophysiologic role.…”
Section: Modifying Factorsmentioning
confidence: 99%